The role of artichoke leaf tincture (Cynara scolymus) in the suppression of DNA damage and atherosclerosis in rats fed an atherogenic diet. (1st January 2018) - Bogavac-Stanojevic, Natasa; Kotur Stevuljevic, Jelena; Cerne, Darko; Zupan, Janja; Marc, Janja; Vujic, Zorica; Crevar-Sakac, Milkica; Sopic, Miron; Munjas, Jelena; Radenkovic, Miroslav; Jelic-Ivanovic, Zorana
Abstract: Context: Polyphenols and flavonoids in artichoke leaf tincture (ALT) protect cells against oxidative damage. Objectives: We examined ALT effects on deoxyribonucleic acid (DNA) damage and lipid profiles in rat plasma and gene expression in rat aorta [haemeoxygenase-1 (HO1), haemeoxygenase-2 (HO2), NADPH oxidase 4 (NOX-4), monocyte chemoattractant protein-1 (MCP-1) and nuclear factor (erythroid-derived 2)-like 2 (Nrf2)]. Materials and methods: Eighteen male Wistar albino rats were divided into three groups ( n = 6/group): The control group (CG) was fed with standard pellet chow for 11 weeks; the AD group was fed for a similar period of time with pellet chow supplemented with 2% cholesterol, 3% sunflower oil and 1% sodium cholate. The ADA group was fed with pellet chow (for 1 week), the atherogenic diet (see above) for the following 4 weeks and then with ALT (0.1 mL/kg body weight) and atherogenic diet for 6 weeks. According to HPLC analysis, the isolated main compounds in ALT were chlorogenic acid, caffeic acid, isoquercitrin and rutin. Results: Normalized HO-1 [0.11 (0.04–0.24)] and MCP-1 [0.29 (0.21–0.47)] mRNA levels and DNA scores [12.50 (4.50–36.50)] were significantly lower in the ADA group than in the AD group [0.84 (0.35–2.51)], p = 0.021 for HO-1 [0.85 (0.61–3.45)], p = 0.047 for MCP-1 and [176.5 (66.50–221.25)], p = 0.020 for DNA scores. HO-1 mRNA was lower in the ADA group than in the CG group [0.30 (0.21–0.71), p = 0.049]. Conclusions: Supplementation with ALT limited the effects of the atherogenic diet through reduced MCP-1 expression, thereby preventing oxidative damage.